Flexicurity: Reconciling Social Security with Flexibility - Empirical Findings for Europe - Hartmut Seifert; Andranik Tangian (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2007)
It is empirically shown that the more flexible employment, the more it is precarious. For this purpose, two families of indices, of flexible work and of precarious work, are defined basing on the Fourth European Survey of Working Conditions 2005 by the European Foundation for the Improvement of Living and Working Conditions. Two methodologies of constructing composite indicators are applied, of the Hans Böckler Foundation, and of the OECD. Both methodologies give very similar results. After the indices have been constructed, the dependence between flexibility and precariousness of work is established by regression analysis with statistical certainty. Besides, it is revealed that the institutional regulation of employment does not necessarily imply the adequate factual effect. For instance, Turkey and Greece with a strict employment protection legislation have a high labour market flexibility due to a large fraction of employees who work with no contract. Among other things, it is shown that the employment flexibility has the strongest negative effect on the employability. It implies serious arguments against the recent reconsideration of the function of social security attempted by the European Commission within the flexicurity discourse. The suggested shift from income security towards a high employability cannot be consistently implemented. Our study provides empirical evidence that a high employability can be hardly attained under flexible employment.
Keywords: C43; J88; J21; C51; 330; Flexicurity; labour flexibility; precarious work; composite indicators; European Commission; European Employment Strategy; Arbeitsmarktflexibilisierung; Ungeschützte Beschäftigung; Soziale Sicherung; Beschäftigungspolitik; EU-Politik; Kritik; EU-Staaten; Europa